KESANTUNAN BERBAHASA SISWA DALAM PBM PASCAPANDEMI COVID’19 DI LINGKUNGAN MADRASAH TSANAWIYAH NEGERI 1 SIMALUNGUN - Eka Sembiring (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2023)
Three years of education in Indonesia can be said to have experienced various shifts caused by COVID-19. There are so many problems that occur, both in terms of cognitive, and affective students. This can be seen clearly from the lack of awareness of students in using greeting words. In fact, there should be a good relationship between teachers and students in the canalization process that occurs. Therefore, several ways are needed to solve the problem. This research uses research methods with a literature study approach (Library Research). This study describes social symptoms that are variables that cause problems to occur. Based on the observations, it appears that the students have very little awareness in the use of language politeness. This can be seen in the lack of use of greeting words. This problem will certainly have a significant effect on student learning and learning motivation.